Myostatin inhibition prevents skeletal muscle pathophysiology in Huntington's disease mice. Issue 1 (December 2017) - Bondulich, Marie; Jolinon, Nelly; Osborne, Georgina; Smith, Edward; Rattray, Ivan; Neueder, Andreas; Sathasivam, Kirupa; Ahmed, Mhoriam; Ali, Nadira; Benjamin, Agnesska; Chang, Xiaoli; Dick, James; et al.
Abstract Huntington's disease (HD) is an inherited neurodegenerative disorder of which skeletal muscle atrophy is a common feature, and multiple lines of evidence support a muscle-based pathophysiology in HD mouse models. Inhibition of myostatin signaling increases muscle mass, and therapeutic approaches based on this are in clinical development. We have used a soluble ActRIIB decoy receptor (ACVR2B/Fc) to test the effects of myostatin/activin A inhibition in the R6/2 mouse model of HD. Weekly administration from 5 to 11 weeks of age prevented body weight loss, skeletal muscle atrophy, muscle weakness, contractile abnormalities, the loss of functional motor units in EDL muscles and delayed end-stage disease. Inhibition of myostatin/activin A signaling activated transcriptional profiles to increase muscle mass in wild type and R6/2 mice but did little to modulate the extensive Huntington's disease-associated transcriptional dysregulation, consistent with treatment having little impact on HTT aggregation levels. Modalities that inhibit myostatin signaling are currently in clinical trials for a variety of indications, the outcomes of which will present the opportunity to assess the potential benefits of targeting this pathway in HD patients.